Development of a Quantitative Assay for the Characterization of Human Collectin-11 (CL-11, CL-K1) - Bayarri-Olmos, Rafael; Kirketerp-Moller, Nikolaj; Pérez-Alós, Laura; Skjodt, Karsten; Skjoedt, Mikkel-Ole; Garred, Peter (Frontiers in Immunology, 2018)
Abstract Collectin-11 (CL-11) is a pattern recognition molecule of the lectin pathway of complement with diverse functions spanning from host defense to embryonic development. CL-11 is found in the circulation in heterocomplexes with the homologous collectin-10 (CL-10). Abnormal CL-11 plasma levels are associated with the presence of disseminated intravascular coagulation, urinary schistosomiasis, and congenital disorders. Although there has been a marked development in the characterization of CL-11 there is still a scarcity of clinical tools for its analysis. Thus, we generated monoclonal antibodies and developed a quantitative ELISA to measure CL-11 in the circulation. The antibodies were screened against recombinant CL-11 and validated by ELISA and immunoprecipitation of serum and plasma. The best candidates were pairwise compared to develop a quantitative ELISA. The assay was validated regarding its sensitivity, reproducibility, and dilution linearity, demonstrating a satisfactory variability over a working range of 0.29 ng/ml–18.75 ng/ml. The mean plasma concentration of CL-11 in healthy controls was determined to be 289.4 ng/ml (range 143.2–459.4 ng/ml), highly correlated to the levels of CL/10/11 complexes (r = 0.729). Plasma CL-11 and CL-10/11 co-migrated in size exclusion chromatography as two major complexes of ~400 kDa and > 600 kDa. Furthermore, we observed a significant decrease at admission in CL-11 plasma levels in patients admitted to intensive care with systemic inflammatory response syndrome. By using the in-house antibodies and recombinant CL-11, we found that CL-11 can bind to zymosan independently of calcium by a separate site from the carbohydrate-binding region. Finally, we showed that CL-11/MASP-2 complexes trigger C4b deposition on zymosan. In conclusion, we have developed a specific and sensitive ELISA to investigate the ever-expanding roles of CL-11 in health and disease and shown a novel interaction between CL-11 and zymosan.